2010
DOI: 10.3141/2190-02
|View full text |Cite
|
Sign up to set email alerts
|

Automated Bicycle Counts

Abstract: Quantifying bicycle use is fundamental to understanding bicycle travel. Methods of counting bicycles vary from limited-time, manual counts to permanent overhead imaging sensors. One common permanent counting method uses inductive loops embedded in the pavement to count cyclists on paths. Although inductive loop detectors have been found to be a highly accurate method of counting bicycles under ideal test conditions, their accuracy after years of use has not been systematically studied. This study focuses on bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…The most common methods are based on pneumatic tubes, inductive loops, passive infrared, automated video counters, infrared cameras and fibre optic pressure sensors (Ryus et al, 2014). Pneumatic and inductive are widespread, but proved to be accurate only when detectors are properly installed, calibrated, maintained, free of external interference, and on a dedicated bicycle lane (Nordback & Janson, 2010). Recently, more innovative counts based on fibre optics register cyclists on mixed traffic lanes, offering insight not only in the cycling volume but also in the speed and direction.…”
Section: Other Point Data Sources: Manual and Automated Countsmentioning
confidence: 99%
“…The most common methods are based on pneumatic tubes, inductive loops, passive infrared, automated video counters, infrared cameras and fibre optic pressure sensors (Ryus et al, 2014). Pneumatic and inductive are widespread, but proved to be accurate only when detectors are properly installed, calibrated, maintained, free of external interference, and on a dedicated bicycle lane (Nordback & Janson, 2010). Recently, more innovative counts based on fibre optics register cyclists on mixed traffic lanes, offering insight not only in the cycling volume but also in the speed and direction.…”
Section: Other Point Data Sources: Manual and Automated Countsmentioning
confidence: 99%
“…Tests of embedded loop detectors in Colorado showed an accuracy of -4% at off-road locations, -3% accuracy on separated paths, and +4% accuracy on shared roadways (Nordback et al 2011;Nordback and Janson, 2010). Testing in New Zealand showed ranges of accuracy from Sensor technology toolbox 87 -10% to +4% for on-road count sites and -10% to +25% for off-road sites (ViaStrada, 2009).…”
Section: Accuracymentioning
confidence: 99%
“…This study addresses a need to evaluate current datasets that may extend the value of bicycle counting programs through volumes contributed by other means. Significant progress in institutionalizing bicycle and pedestrian monitoring has been made in Colorado, Minnesota, and Oregon, and agencies are searching for efficient solutions to fill this need (Lindsey, Nordback, and Figliozzi 2014;Nordback and Janson 2010;. A recent Transportation Research Board circular summarized a number of recent and ongoing studies in the realm of active transportation monitoring methods and identified a need to continue research in crowdsourced volume data sources (Griffin, Nordback, Götschi, Stolz, and Kothuri 2014).…”
Section: Introductionmentioning
confidence: 99%